(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Television industrial organization is probably more complex than in other media industries. Reasons behind include that it is newer than others, it is highly regulated and because many changes have taken place in a short time period. In particular, public service television deserves an in-depth study. This is the starting point of this piece of research, which is applied to children as an audience of a growing complex and competitive market. In doing so, this study focuses on public service broadcasters of three European countries: the United Kingdom, Italy and Spain. A correlation analysis of these three cases will be made and the main hypothesis is that the content of all three channels and their audience profiles is quite similar. It will be implemented by Research Group on Digital Information and Communication (GICID, University of Zaragoza) and Research and Learning of Media and Communications Management (MediaCom, Complutense University of Madrid).